Actions and orientations of the primary health care nurse in the prevention of the diabetic foot - Souza, Jailsa Maria da Silva; Soares, Jandson de Oliveira; Pontes, Alessandra Nascimento (JRG Journal of Academic Studies, 2023)
Diabetic foot lesions are a problem that needs increasing and constant attention due to its severity and the high number of diabetics who develop such complication as a result of poor health education. The lack of foot surveillance in diabetics is an existing problem that limits the identification of risk factors, prevention and timely intervention. To solve this problem, it is necessary for nurses to master and exercise surveillance and injury risk assessment procedures. The aim of this study is to analyze the literature already published on Diabetes Mellitus and the Diabetic Foot, focusing on the practices of care and prevention of the diabetic foot. This work is a bibliographic study of the integrative review type, carried out in the main scientific databases present in the Virtual Health Library, BDENF, Lilacs and Medline. The guiding question was: What are the nursing care skills of nurses facing a patient with diabetic foot? The synthesis of the collected evidence points out that the nurse’s performance in Primary Health Care is an important strategy to prevent complications among those who live with diabetes. The studies reveal potentiality regarding the educational practice of this professional for the prevention of the diabetic foot. Thus, we can conclude that nurses are indispensable tools in the process of health education and can contribute to the prevention of the diabetic foot. Therefore, this work aims to contribute to the knowledge of diabetics and nursing professionals.